LEARNING STYLE TENDENCY IN STUDENTS SPEAKING ACTIVITY: AUDIO AND VISUAL - Nelsa Amanda Maharani; Lintang Rizki Wardhani; Sharifah Fazira Izroin; Rini Estiyowati Ikaningrum (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2022)
This study examines the learning styles' tendency between visual and auditory toward English speaking ability. The respondents came from the 5th-semester students from Universitas Tidar who participated in this research. The method used is a non-experimental quantitative method regarding the scientific method. This research will be analyzed using a Likert scale which shows that there are different influences on the ability to speak English visually and auditory. The visual learning style produces the most significant percentage gain of 56.65%. The auditory learning style gets the smallest percentage of 45%. Implications from the result of this study, in speaking ability, a person can give a tendency for visual learning styles followed by auditory ones, which influence English Education Students of Universitas Tidar.